2010
DOI: 10.1007/s10964-009-9502-0
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Victimization and Adolescent Self-Harm: Testing Hypotheses from General Strain Theory

Abstract: Self-harm is widely recognized as a significant adolescent social problem, and recent research has begun to explore its etiology. Drawing from Agnew's (1992) social psychological strain theory of deviance, this study considers this issue by testing three hypotheses about the effects of traditional and cyber bullying victimization on deliberate self-harm and suicidal ideation. The data come from a school-based survey of adolescents in a rural county of a southeastern state (n = 426); 50% of subjects are female,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
222
6
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 332 publications
(247 citation statements)
references
References 50 publications
17
222
6
2
Order By: Relevance
“…This finding corroborates emerging past studies that relied on student samples and have found that bullying victimization has an important relationship with not only aggression directed towards others but also with aggression directed towards oneself Hay and Meldrum, 2010). Our findings add to the extant literature and underscore the harmful effect of bullying (Finkelhor et al, 2005;Storch and Ledley, 2005).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding corroborates emerging past studies that relied on student samples and have found that bullying victimization has an important relationship with not only aggression directed towards others but also with aggression directed towards oneself Hay and Meldrum, 2010). Our findings add to the extant literature and underscore the harmful effect of bullying (Finkelhor et al, 2005;Storch and Ledley, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Various studies (Rothon et al, 2012;Smokowski and Bacallao, 2007) and systematic reviews (Bigby, 2012;Jennings et al, 2014) have documented the positive effect of social support in enhancing mental health and well-being of adolescents. Hay and Meldrum (2010) found that a combination of social support and self-control provides adolescents with the ability to deliberate on their stressful life situation and avoid taking actions that might be deleterious to their mental health and well-being. Efforts aimed at preventing NSSI should first identify and reduce risk factors for NSSI while at the same time identifying and increasing factors found to be associated with a diminished likelihood of engaging in NSSI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Nevertheless, bullying is still poorly understood and is characterized by some degree of permissiveness and indifference in the school environment, with little attention paid to the negative consequences that can later contribute to the development of antisocial conducts. 5 Authors have described the impact of bullying on the physical and psychological health of victims, reporting increased rates of mental disorders, 6 self-mutilation, 7 suicidal ideation, 7 and substance use/abuse 8 in this population. There is evidence that adolescent bullying may affect quality of life, posing physical and emotional difficulties not only to victims but also to perpetrators.…”
Section: Introductionmentioning
confidence: 99%